Histone H3.3 G34 Mutations Alter Histone H3K36 and H3K27 Methylation In Cis - Shi, Leilei; Shi, Jiejun; Shi, Xiaobing; Li, Wei; Wen, Hong (Journal of molecular biology, 2018)
Histone H3 encoding genes, particularly H3F3A and H3F3B, the genes encoding the variant histone H3.3, are mutated at high frequency in pediatric brain and bone malignancies. Compared to the extensive studies on K27M and K36M mutations, little is known about the mechanism of G34 mutations found in pediatric glioblastoma or giant cell tumors of the bone. Here we report that unlike the K27M or K36M that affect global histone methylation, the giant cell tumors of the bone G34 mutations (G34L/W) only affect histone H3K36 and H3K27 methylation on the same mutated histone tails (in cis), a mechanism distinct from known histone mutations. [Display omitted] •Giant cell tumors of the bone (GCTB) H3.3G34 mutations (G34L/W) only affect histone H3K36 and H3K27 methylation on the same mutated histone tails (in cis).•GCTB H3.3G34 mutations (G34L/W) inhibits SETD2 enzymatic activity.•GCTB H3.3G34 mutations (G34L/W) do not affect the enzymatic activity of EZH2 or p300.•GCTB H3.3G34 mutations (G34L/W) affect histone H3K36 and H3K27 methylation readers binding to chromatin.